Loss of Wwox Perturbs Neuronal Migration and Impairs Early Cortical Development - Iacomino, Michele; Baldassari, Simona; Tochigi, Yuki; Kośla, Katarzyna; Buffelli, Francesca; Torella, Annalaura; Severino, Mariasavina; Paladini, Dario; Mandarà, Luana; Riva, Antonella; Scala, Marcello; Balagura, Ganna; et al. (Frontiers in Neuroscience, 2020)
Mutations in the WWOX gene cause a broad range of ultra-rare neurodevelopmental and brain degenerative disorders, associated with a high likelihood of premature death in animal models as well as in humans. The encoded Wwox protein is a WW domain-containing oxidoreductase that participates in crucial biological processes including tumour suppression, cell growth/differentiation and regulation of steroid metabolism, while its role in neural development is less understood. We analyzed the exomes of a family affected with multiple pre- and postnatal anomalies, including cerebellar vermis hypoplasia, severe neurodevelopmental impairment and refractory epilepsy, and identified a segregating homozygous WWOX mutation leading to a premature stop codon. Abnormal cerebral cortex development due to a defective architecture of granular and molecular cell layers was found in the developing brain of a WWOX-deficient human foetus from this family. A similar disorganization of cortical layers was identified in lde/lde rats (carrying a homozygous truncating mutation which disrupts the active C-terminal domain) investigated at perinatal stages. Transcriptomic analyses of Wwox-depleted human neural progenitor cells showed an impaired expression of a number of neuronal migration-related genes encoding for tubulins, kinesins and associated proteins. These findings indicate that loss of Wwox may affect different cytoskeleton components and alter prenatal cortical development, highlighting a regulatory role of the WWOX gene in neural progenitor cells and migrating neurons across different species.